Bionanoparticles in cancer imaging, diagnosis, and treatment. Issue 4 (15th March 2022) - Li, Yan; Bao, Qing; Yang, Shuxu; Yang, Mingying; Mao, Chuanbin
Abstract: Biological molecules such as DNA, proteins, and lipids can be assembled into naturally existing nanoparticles, such as bacterial viruses (also called bacteriophages or phages), plant viruses, nucleic acid nanoparticles (e.g., DNA origami), protein nanoparticles, and exosomes. These bionanoparticles have their own distinct properties (including compositions, structures, shapes, and functions), laying the foundation for their unique applications as probes for cancer imaging, as detectors for cancer diagnosis, or as therapeutics for cancer therapy. To highlight how the distinct properties of different bionanoparticles can be explored in cancer nanotheranostics, this review critically analyzed the use of bionanoparticles in cancer imaging, diagnosis, and treatment. Specifically, for each of these representative bionanoparticles, we describe its unique properties that render it powerful in cancer theranostics compared with synthetic inorganic nanoparticles. We also summarize how to genetically or chemically modify or redesign the bionanoparticles so that they gain new functions desired for cancer theranostics, such as tumor‐seeking or tumor‐destructive capabilities. Finally, we discussed the challenges in this exciting field. The bionanoparticles covered in this review represent different biomolecular assemblies with unique theranostic applications, showcasing the power of bionanoparticles in disease diagnosis and treatment. Abstract : The natural and artificial biological molecules, such as the DNA, proteins, and lipids, could be assembled into bionanoparticles such as bacterial viruses (i.e., bacteriophages or phages), plant viruses, DNA origami, protein nanoparticles, and exosomes. Here, we review their applications in cancer imaging, diagnosis, and treatment and highlight their distinct properties.